An investigation of changing socio-economic conditions, opportunities and development interventions in small Eastern Cape towns in South Africa - Keal, Duncan (Rhodes University, Faculty of Science, Department of Geography, 2009)
Small towns internationally and in South Africa are becoming increasingly marginalised, and they are often experiencing economic downturn, demographic shifts and a rearticulation of their role in the urban hierarchy. In the case of South Africa many of these small towns are also faced with low levels of social development. The urgent need to address such conditions is evident by the fact that a large proportion of the South African population resides in small towns, and their surrounding hinterlands. This said, there are examples of small towns, internationally and in South Africa which, through the use of various Local Economic Development actions, have managed to remain sustainable, and in some cases become economically viable localities once again. In light of the above, the research conducted for this thesis seeks first to establish the socio-economic changes occurring over time in three small towns in the Eastern Cape Province of South Africa, namely Stutterheim, Bedford and Hamburg. Secondly, the research aims to identify the nature of LED activities in the three small towns, highlighting those factors contributing to the success of LED initiatives as well as those factors inhibiting LED in small towns. This is done with the intention of developing future lessons for LED in small towns. The research was conducted using a mix of qualitative and quantitative data generated through the interviews with key role players in each town, as well as secondary data sources. Findings from the research suggest that the small towns investigated are characterised by low levels of socio-economic development. In addition, it appears that the development opportunities for the towns are limited. Current initiatives are being driven by private role players with local government being largely uninvolved. Such initiatives are limited in nature, with benefits only felt by small groups of the local community. However, examples do exist of where LED has successfully benefited the broader spheres of the local community, thus suggesting that if implemented properly such an approach does have potential to assist in the socio-economic development of small towns. In light of this, a number of lessons are identified for LED in small towns, including the need for strong leadership, community involvement, partnerships between role players, and planning for project sustainability.
Keywords: Local Economic Development (Programme); Economic development -- South Africa -- Eastern Cape -- Case studies; Sustainable development -- South Africa -- Eastern Cape -- Case studies; Community development -- South Africa -- Eastern Cape -- Case studies; Cities and towns -- South Africa -- Eastern Cape -- Growth; South Africa -- Economic conditions